The Effect Of The Problem Based Learning Model On The Scissors Style High Jump At SMPN 1 Kramatmulya - Al Imron Maulana; Elang Fauzan (Jurnal Pendidikan Jasmani (JPJ), 2026)
This research is motivated by the low ability of high jump, especially in scissors style, in students, which is caused by a lack of understanding of the basic techniques of high jump and less than optimal training provided by teachers. Teachers tend to choose other sports so that athletics is slightly behind in students' understanding, especially in the high jump athletics branch and tend to provide comprehensive examples without focusing on structured learning. This study aims to improve high jump skills, especially in scissors style, through the application of a problem-based learning approach. The method used in this study is an experiment with a pretest and posttest design in one group. The research sample consisted of 31 students of class VIII E, taken randomly from a population of 245 students of class VIII at SMP Negeri 1 Kramatmulya, Kuningan Regency. This study used a cluster random sampling technique, a high jump ability test for scissors style was used as a measurement tool. The results showed that a problem-based learning approach can significantly improve high jump skills, especially in scissors style in students. Problem solving in the learning process helps students apply more specific targets, which ultimately improves high jump skills in scissors style. This research is expected to be able to integrate technology as an innovation in high jump learning to improve students' skills in athletics, especially in the high jump event in the scissors style.